Relativistic Astrophysics and Cosmology – Einstein’s Legacy Proceedings of the MPE/USM/MPA/ESO Joint Astronomy Conference Held in Munich, Germany, 7-11 November 2005 - Aschenbach, Bernd; Burwitz, Vadim; Hasinger, Günther; Leibundgut, Bruno; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
"Relativistic Astrophysics and Cosmology" have developed into important and fruitful research areas with a hitherto unprecented public interest. The year 2005, which marked the 100th anniversary of the 'annus mirabilis', that year in which Albert Einstein published three of his most important scientific papers, was the perfect opportunity to review and to present the current scientific understanding of relativistic topics including cosmological models, cosmology related measurements, the large scale properties of the Universe, dark matter and dark energy, the theory of gravity, black holes, theory and measurements, active galactic nuclei, clusters of galaxies, jets. Each of these subjects is addressed and the book represents a useful reference tool both for the expert and the new-comer in these fields.
Cosmology -- Gravity -- Black Holes -- Active Galactic Nuclei -- Clusters of Galaxies -- Gamma Ray Bursts -- X-ray Binaries and Jets -- Conference Summary.
Keywords: Cosmology; Gravitation; Astronomy; Astrophysics; Cosmology; Classical and Quantum Gravitation, Relativity Theory; Astronomy, Astrophysics and Cosmology